Assessment of Self-Activation and Inhibition of Wheat Coiled-Coil Domain Containing NLR Immune Receptor Yr10CG - Nan Wu; Wanqing Jiang; Zhaoxia Xiang; Raheel Asghar; Mahinur S. Akkaya (Plants)
Plant immunity is largely governed by nucleotide-binding leucine-rich repeat receptor (NLR). Here, we examine the molecular activation and inhibition mechanisms of the wheat CC-type NLR Yr10CG, a previously proposed candidate for the Yr10 resistance gene. Though recent studies have identified YrNAM as the true Yr10 gene, Yr10CG remains an important NLR in understanding NLR-mediated immunity in wheat. In this study, we found that the overexpression of either the full-length Yr10CG or its CC domain in Nicotiana benthamiana did not trigger cell death, suggesting a robust autoinhibitory mechanism within Yr10CG. However, we observed that mutations in the conserved MHD motif, specifically D502G, activated Yr10CG and induced cell death. Structural modeling indicated that this mutation disrupted key interactions within the MHD motif, promoting local flexibility and activation. We further explored the effector recognition potential of Yr10CG by creating chimeric proteins with Sr50 domains, revealing that both the NB-ARC and LRR domains are necessary for effector recognition, while the CC domain likely functions in downstream immune signaling. Additionally, disrupting membrane localization through an L11E mutation abolished Yr10CG self-activation, suggesting a requirement for membrane association in immune activation. Our findings contribute to the understanding of CC-NLR activation and autoinhibition mechanisms, highlighting the potential of Yr10CG in NLR engineering for crop resistance improvement.